The effects of the removal of diesel subsidy on lorry operators with special reference to Wilayah Persekutuan and Port Klang - Mohd. Yusuf, Abdul Aziz; Sahat, Affendi; Abu Bakar, Mazni; Abdullah, Azizah; Ithnain, Shamsiah (1984)
Through the years, diesel has been an important item as a low-saving fuel to the lorry operators. Unfortunately, on 1st January 1984 the price of diesel increased following the removal of Diesel Subsidy by the government. This has left some substantial impact on the transport users. Sensitive to the situation, we are stimulated to study the effects of the removal of Diesel Subsidy mainly on lorry 'A' operators. The effects we are interested is not only directly on lorry operators but, also indirectly to the relative sectors of lorry operation, for example, the lorry transport users or hirers and the consumers.